Penial morphology in three species of Brazilian Tuco-tucos, Ctenomys torquatus, C. minutus, and C. flamarioni (Rodentia: Ctenomyidae) Morfologia peniana de três espécies de tuco-tuco do Brasil - Ctenomys torquatus, C. minutus e C. flamarioni (Rodentia: Ctenomyidae) - O. Rocha-Barbosa; JSL. Bernardo; MFC. Loguercio; TRO. Freitas; JR. Santos-Mallet; CJ. Bidau (Brazilian Journal of Biology, 2013)
The present study analyses the glans penis and baculum morphology of three Brazilian tuco-tucos, Ctenomys torquatus Lichtenstein, 1830, Ctenomys minutus Nehring, 1887 and Ctenomys flamarioni Travi, 1981, in order to identify possible variations and understand some more about this taxonomically complex group. We used fixed penis from 15 previously listed adult specimens. For a more detailed baculum analysis, the penis underwent dissection and diaphanisation, whereas to analyse the glans penis surface we used Scanning Electron Microscopy (SEM). Results showed striking differences in baculum morphology among the three species. While C. minutus have a particular V-shaped proximal baculum tip, C. flamarioni baculum is thin throughout the shaft with rounded proximal and distal tips. Ctenomys torquatus have a shorter and larger baculum, similar to what has previously been described for the species. Glans penis surface microstructure analyses also revealed inter-specific differences, with penial spines varying in shape, size and, especially density. Although C. torquatus has a relatively small penis, it has the largest penial spine density, which suggests a more complex penial ornamentation in this species. O presente estudo analisa a morfologia do glans penis e do baculum de três tuco-tucos do Brazil - Ctenomys torquatus Lichtenstein, 1830, Ctenomys minutus Nehring, 1887, e Ctenomys flamarioni Travi, 1981 - com a finalidade de identificar possíveis variações e elucidar mais sobre grupo taxonômico complexo. Foram usados pênis fixados de 15 indivíduos adultos das espécies listadas anteriormente. Para uma análise mais detalhada do baculum, o pênis foi submetido a dissecções e diafanização, enquanto que, para a análise da superfície do glans penis, foi usada a técnica de microscopia eletrônica de varredura (MEV). Os resultados exibiram significativas diferenças na morfologia do baculum entre as três espécies. Enquanto C. minutus apresenta um baculum com uma ponta em forma de V característica, o baculum de C. flamarioni é fino ao longo do osso, com as pontas proximal e distal arredondadas. Ctenomys torquatus apresenta um baculum mais curto e largo, similar ao descrito anteriormente para a espécie. Análises da microestrutura na superfície do glans penis revelaram diferenças interespecíficas, com os espinhos penianos variando em forma, tamanho e, especialmente, densidade. Apesar de C. torquatus ter um pênis relativamente pequeno, apresenta a maior densidade de espinhos penianos, o que sugere uma complexa ornamentação peniana nesta espécie.